The Effectiveness of Using Neymar Jr. as a Brand Ambassador for Mister Potato Products on Instagram Social Media - Ronaldo Budialim; Felicia Goenawan (Journal of Content and Engagement, 2023)
Mister Potato, a prominent potato chip brand originating from Malaysia, was established in 1992 and has since secured its position as the leading snack choice in Malaysia. As part of its 30th-anniversary celebrations, Mister Potato proudly appointed the globally renowned football athlete Neymar Jr. as its brand ambassador. This study endeavors to evaluate the efficacy of Neymar Jr. in his role as the brand ambassador for Mister Potato. Employing a survey method facilitated through the Likert scale, the researchers collected responses until reaching a sample size of 100 respondents. The assessment of effectiveness was carried out using the VisCAP model. The outcomes of this research unequivocally affirm the effectiveness of Neymar Jr. as a brand ambassador for Mister Potato.